2004
DOI: 10.1016/j.jacc.2003.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcome in aortic sclerosis is associated with coronary artery disease and inflammation

Abstract: The increased incidence of adverse cardiovascular events in patients with aortic sclerosis is associated with coronary artery disease and inflammation, not a result of the effects of valvular heart disease per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
2
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 26 publications
1
76
2
8
Order By: Relevance
“…These studies have consistently suggested that determination of AVCS by CT has a good correlation with the severity of aortic stenosis. [11][12][13] After this, several studies also suggested that the severity of aortic sclerosis 2) and AVCS in aortic stenosis, 14) respectively, could be used as predictors of adverse cardiovascular events. These fi ndings were explained by the fact that aortic sclerosis and coronary artery calcifi cation shared the common risk factors of atherosclerosis, 4,15) and the disease spectrum of sclerosis to stenosis in the aortic valve was akin to the process of coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have consistently suggested that determination of AVCS by CT has a good correlation with the severity of aortic stenosis. [11][12][13] After this, several studies also suggested that the severity of aortic sclerosis 2) and AVCS in aortic stenosis, 14) respectively, could be used as predictors of adverse cardiovascular events. These fi ndings were explained by the fact that aortic sclerosis and coronary artery calcifi cation shared the common risk factors of atherosclerosis, 4,15) and the disease spectrum of sclerosis to stenosis in the aortic valve was akin to the process of coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiologic studies have suggested that aortic sclerosis has clinical value regarding the prediction of adverse cardiovascular outcomes, 2,3) and these suggestions are evidenced by common risk factors and histologic characteristics of atherosclerosis. 4) However, the defi nition of aortic sclerosis is obscure and its qualitative nature which depends on a subjective description by echocardiography, such as focal thickening or increased echogenicity, 5) makes limitations on clinical application.…”
mentioning
confidence: 99%
“…Rather than adverse outcomes as a consequence of the primary valvular disorder, it has been proposed that aortic sclerosis may represent a surrogate marker either for underlying atherosclerotic disease 44,45 or some generalized systemic process, such as inflammation. [45][46][47][48] Supporting evidence for a surrogate marker for atherosclerosis comes from the cardiac catheterization laboratory, where up to 50% of patients with severe aortic stenosis undergoing preoperative evaluation for valve replacement are diagnosed with concurrent significant coronary artery disease.…”
Section: Clinical Outcomes In Adults With Aortic Sclerosismentioning
confidence: 99%
“…Attention has recently been focused on the inflammatory reaction as a factor for predicting the risk to the cardiovascular system. [1][2][3] It has been reported that the use of highly sensitive C-reactive protein (hs-CRP), an inflammatory marker, facilitated the quantitative measurement of CRP at a higher sensitivity, even if the CRP levels measured by using conventional methods appeared to remain within the normal range. [4][5][6][7][8][9] In addition, the risk of initially developing myocardial infarction has been reported to increase significantly with the elevation of the hs-CRP levels.…”
mentioning
confidence: 99%